Hubungan antara ekspresi Vascular Endothelial Growth Factor (VEGF) dengan karakteristik klinikopatologi osteosarkoma di RSUP Sanglah Denpasar, Bali - Johanes Prasetyo Harjanto; I Wayan Juli Sumadi; I Made Gotra; Ni Putu Ekawati (DiscoverSys Inc., 2021)
Background: Osteosarcoma is the most common malignant primary bone tumor. Although osteosarcoma cases are relatively rare compare to carcinoma, the mortality rate is quite high. Osteosarcoma prognosis can be seen from conventional pathology and biological markers, such as Vascular Endothelial Growth Factor (VEGF). In various studies, the presence of VEGF expression has been associated with the worsening prognosis of osteosarcoma. This study aims to determine the relationship between VEGF expression and osteosarcoma's clinicopathological characteristics at Sanglah General Hospital, Denpasar, 2015-2019.Method: This research is a cross-sectional analytic study. The sampling technique used all affordable populations that were included in the inclusion criteria, with a total sample of 30 samples. The research data used secondary data obtained from the archive of histopathological examination reports at the Anatomical Pathology Laboratory at Sanglah General Hospital and paraffin blocks from all available samples for immunohistochemical examination. Data were analyzed using SPSS version 22 for Windows.Results: The clinicopathological characteristics of the osteosarcoma studied were age, tumor location, histological type, and grading. Patients with osteosarcoma in this study were predominantly found in the age group <20 years (66.67%), femur locations (60.00%), mixed type osteosarcoma (53.33%), and high grade (100.00%). A total of 26 samples (86.67%) had high VEGF expression and 4 samples had low VEGF expression (13.30%). There was no significant relationship between age (p=0.241), location of the tumor (p=0.739), and histological type (p=1.000) to the VEGF expression.Conclusion: The relation between each osteosarcoma clinicopathological characteristic associated with VEGF expression showed insignificant results in age, location, and histological type. Further research is needed with a more significant number of samples to get better results. Latar Belakang: Osteosarkoma adalah tumor tulang primer ganas yang paling umum. Meskipun kasus osteosarkoma relatif jarang dibandingkan dengan karsinoma, angka kematiannya cukup tinggi. Prognosis osteosarkoma dapat dilihat dari patologi konvensional dan penanda biologis, salah satunya adalah Vascular Endothelial Growth Factor (VEGF). Dalam berbagai penelitian, kehadiran ekspresi VEGF telah dikaitkan dengan prognosis yang memburuk dari osteosarcoma. Penelitian ini bertujuan untuk mengetahui hubungan ekspresi VEGF dengan karakteristik klinikopatologi osteosarkoma di RSUP Sanglah Denpasar tahun 2015-2019.Metode: Penelitian ini merupakan penelitian analitik potong lintang. Teknik pengambilan sampel menggunakan semua populasi terjangkau yang termasuk dalam kriteria inklusi, dengan jumlah sampel sebanyak 30 sampel. Data penelitian menggunakan data sekunder yang diperoleh dari arsip laporan pemeriksaan histopatologi di Laboratorium Patologi Anatomi RSUP Sanglah dan blok parafin dari semua sampel yang tersedia untuk pemeriksaan imunohistokimia. Data dianalisis dengan SPSS versi 22 untuk Windows.Hasil: Karakteristik klinikopatologi dari osteosarkoma yang diteliti adalah usia, lokasi tumor, tipe histologis, dan grading. Penderita osteosarkoma pada penelitian ini paling banyak ditemukan pada kelompok usia <20 tahun (66,67%), lokasi femur (60%), tipe campuran osteosarkoma (53,33%) dan High-Grade (100.00%). Sebanyak 26 sampel (86,67%) memiliki ekspresi VEGF tinggi dan 4 sampel memiliki ekspresi VEGF rendah (13,30%). Tidak terdapat hubungan yang bermakna antara usia (p=0,241), lokasi (p=0,739), dan tipe histologis (p=1,000).Kesimpulan: Hubungan antara masing-masing karakteristik klinikopatologi osteosarkoma yang terkait dengan ekspresi VEGF menunjukkan hasil yang tidak bermakna pada usia, lokasi, dan tipe histologis. Diperlukan penelitian lebih lanjut dengan jumlah sampel yang lebih banyak untuk mendapatkan hasil yang lebih baik.